Development of a Web-Based School Library System at SMPN 57 Bandung - Raka Aprianto; Muhammad Alam Fajar; Revellino Yoel; Dhafa Ferdhiansyah; Luthfi Ardyansyah (Jurnal Indonesia Sosial Teknologi, 2025)
School libraries serve as fundamental pillars in the educational ecosystem, providing essential resources and services that support both teaching and learning processes across all academic levels. However, the persistent reliance on manual management systems continues to present significant challenges, including inefficiencies in data processing, increased susceptibility to human error, reduced accuracy in record-keeping, and substantial time consumption in routine administrative tasks. This community service research aims to design, develop, and implement a comprehensive web-based library management system to address the operational challenges faced by SMPN 57 Bandung, specifically targeting improvements in book cataloging, borrowing procedures, return processes, and overall administrative efficiency. The methodology employed a systematic waterfall development approach, incorporating comprehensive needs analysis, user-centered design principles, iterative testing protocols, and stakeholder engagement throughout the development lifecycle. The system was developed using the PHP programming language with the CodeIgniter framework and MySQL database management. This system includes features such as book information, borrowing data, returning, and an admin dashboard. The implementation results demonstrate significant improvements in operational efficiency, with transaction processing time reduced from an average of 5 minutes to less than 1 minute per transaction, elimination of data duplication errors, and enhanced user satisfaction among both library staff and students. These findings have broader implications for digital transformation in educational institutions, particularly in developing cost-effective solutions for resource management challenges commonly faced by Indonesian schools.